2014
DOI: 10.1039/c4fo00071d
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activity of a flavonoid-rich concentrate recovered from Opuntia ficus-indica juice

Abstract: In this work, Opuntia ficus indica juice was explored as a potential source of natural antioxidant and anti-inflammatory ingredients towards intestinal inflammation. An adsorption separation process was used to produce a natural flavonoid-rich concentrate (FRC) from Opuntia ficus-indica juice. The FRC effect (co- or pre-incubation) on induced-oxidative stress and induced-inflammation was evaluated in human Caco-2 cells. The main constituents identified and present in the extract are flavonoids (namely isorhamn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 35 publications
2
38
0
2
Order By: Relevance
“…Although present in all tissue extracts, its presence was highest in peel extracts with values of 8776.5, 7977.8, 5390.3, 6562.8, 6758.2, and 7243.1 μg mL −1 extract in Morada, Sanguinos, Verdal, Pelota, Vigor, and Diamante varieties, respectively. Recent studies have also identified piscidic acid as one of the main constituents in prickly pear fruit juices along with ferulic acid and eucomic acids, but they have not quantified this compound due to the unavailability of commercial standards.…”
Section: Resultsmentioning
confidence: 99%
“…Although present in all tissue extracts, its presence was highest in peel extracts with values of 8776.5, 7977.8, 5390.3, 6562.8, 6758.2, and 7243.1 μg mL −1 extract in Morada, Sanguinos, Verdal, Pelota, Vigor, and Diamante varieties, respectively. Recent studies have also identified piscidic acid as one of the main constituents in prickly pear fruit juices along with ferulic acid and eucomic acids, but they have not quantified this compound due to the unavailability of commercial standards.…”
Section: Resultsmentioning
confidence: 99%
“…31 Inhibition of the activity of cytokines represents a therapeutic strategy for IBD. [35][36][37] The first objective of the study was to compare the bioaccessibility and intestinal cellular uptake of GABA, γ-oryzanol, vitamin E and phenolic acids in digested BR and PGBR using the coupled in vitro digestion method and the Caco-2 human intestinal cell model. 34 Consequently, there is increased interest in the identification of dietary compounds that are relatively safe and affordable for the treatment of inflammatory bowel disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, the phenolic including flavonoids and betalain profiles of juice obtained from the wild fruits of O. ficus-indica collected in Alentejo [Marvão (Portalegre), Sines (Setúbal) Beja and Ribatejo [Tramagal (Santarém)] were recently studied, as well as their potential as antioxidants, anti-inflammatory and antiproliferative agents (Mata et al, 2016;Matias et al, 2014;Serra, Poejo, Matias, Bronze, & Duarte, 2013).…”
mentioning
confidence: 99%